Pengaruh Faktor Lingkungan terhadap Penyakit Asma di Indonesia - Oemiyati, Ratih; Alwi, Qomariah (Pusat BTDK, 2009)
Over the world asthma is included in the 5 highest cause of morbidity and mortality (prevalence between 5-30%), and the 10 highest cause of morbidity and mortality in Indonesia (around 2-5%). Some researches show that environmental factors influence the prevalence asthma. The objective of this research is to find the asthma prevalence in Indonesia by province, and to evaluate the relationship between asthma and environmental factors (contact with livestock, smoking and the distance between the house and pollution sources). Data were obtained from the Basic Health Research (Riskesdas) 2007 and be analyzed by the methods of univariate and bivariate. The research result shows that asthma prevalence in Indonesia is 3.32%. The highest prevalence is in Gorontalo province (7.23%) and the lowest prevalence is in DI Aceh (0.09%). It is found that contact with livestock, smoking and the distance between the house and pollution sources (solid waste dumping sites, industries, and workshops) have significant relationship to asthma. But the distance between the house and road, traditional market, and terminal/train station/airport did not influence asthma. Â Key words: environmental factors, asthma, Indonesia.